2001
DOI: 10.2116/analsci.17.51
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Reaction of Pu3+/Pu Couple in LiCl-KCl Eutectic Melts: Comparison of the Electrode Reaction at the Surface of Liquid Bi with That at a Solid Mo Electrode

Abstract: Pyrochemical reprocessing of nuclear fuels using molten salt as a solvent shows promise for advanced nuclear engineering because of its compactness, economy, radiation resistance and nonproliferation. 1 In the electrorefining process, which is a key step in pyrochemical reprocessing, spent fuels are anodically dissolved in LiCl-KCl eutectic melt, and U, Pu and minor actinides (MAs; Np, Am, Cm, etc.) are recovered together at the cathode. 2,3 It has been proposed that U could be selectively recovered at the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 24 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Electrochemical behavior of U͑IV͒ was reported in several investigations. [1][2][3][4][5][6][7][8] Electroreduction of UCl 4 in LiCl-KCl eutectic melt proceeds in two steps involving transfer of one and three electrons, respectively. The reversibility of the reduction of U͑IV͒ to U͑III͒ was evidenced by the chronopotentiometry method 1 and confirmed by cyclic voltammetry measurements.…”
mentioning
confidence: 99%
“…Electrochemical behavior of U͑IV͒ was reported in several investigations. [1][2][3][4][5][6][7][8] Electroreduction of UCl 4 in LiCl-KCl eutectic melt proceeds in two steps involving transfer of one and three electrons, respectively. The reversibility of the reduction of U͑IV͒ to U͑III͒ was evidenced by the chronopotentiometry method 1 and confirmed by cyclic voltammetry measurements.…”
mentioning
confidence: 99%
“…Among actinides, plutonium was chosen as element of study. In chloride media, electrochemical studies were carried out on PuCl 3 on inert electrode in LiCl-KCl by Serp et al [10] and O. Shirai et al [11,12]. They found that Pu(III) reduction proceeds via a one-step process with 3 electrons exchanged.…”
Section: ) As Nuclear Fuel [4e6]mentioning
confidence: 99%
“…This pyrochemical process shows promise for an advanced nuclear engineering design because of its compactness, economy, radiation resistance and nonproliferation [2]. Of all the unit operations of a pyrochemical process, an electrorefining is a key step [2,3].…”
Section: Introductionmentioning
confidence: 99%